Effects of behavioural change communication on HIV and AIDS related high risk behaviour among fishermen in Homabay and Siaya Counties, Kenya - Akobi, William Kala; Oyore, John Paul; Otieno, George Ochieng (International Journal Of Community Medicine And Public Health, 2022)
Background: Risky sexual behaviors such as sexual concurrency, sexual networks (fish for sex exchange) and unprotected sex, have been reported as the main cause of sexually transmitted diseases (STIs) /HIV infections among fisher folks. Behavioral change mechanisms as condom use and abstinence are some of interventions used in prevention HIV/AIDS spread in Kenya. Risky sexual behaviors increase risk of contracting STIs including HIV/AIDS Methods: This was a cross-sectional descriptive study involving 246 randomly selected fisher folks in Mbita- and Usenge along Lake Victoria. The survey used questionnaires to collect data among respondents. Using a sample frame in the beach management unit offices, fisherfolks were identified and invited to participate. Consent was obtained from participants Results: The mean age of respondents was 31 years old. The 72% of the participants were directly involved in fishing. Participants who had extra marital relationship though married were 56.1% in Mbita and 47% in Usenge. Respondents who took alcohol with friends were 94.1% in Mbita and 96.2% in Usenge. Respondents who indicated that they had unprotected sex under influence of alcohol were 48.3% in Mbita and 77.1% in Usenge. Those who were sexually taken advantage of while under the influence of alcohol were 23.8% in Mbita and 38.3% in Usenge while those had sexually taken advantage of under the influence of alcohol were 18.3% in Mbita and 37.8% in Usenge. Conclusions: Targeted behaviour change communication (BCC) strategies designed specifically for fisherfolks is needed to curb high incidences of risky sexual behaviours noted among the fishermen.